BLEVE overpressure: Multiscale comparison of blast wave modeling. Issue 3 (17th September 2013) - Laboureur, D.; Heymes, F.; Lapebie, E.; Buchlin, J.M.; Rambaud, P.
<x xml:space="preserve">Abstract</x> BLEVE overpressure modeling has been already widely studied but only few validations including the scale effect have been made. After a short overview of the main models available in literature, a comparison is done with different scales of measurements, taken from previous studies or coming from experiments performed in the frame of this research project. A discussion on the best model to use in different cases is finally proposed. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 274–284, 2014